Major adverse cardiovascular events while awaiting staged non-culprit percutaneous coronary intervention after ST-segment elevation myocardial infarction. Issue 1 (2nd January 2019) - McCutcheon, Keir; Triantafyllis, Andreas S.; Marynissen, Thomas; Adriaenssens, Tom; Bennett, Johan; Dubois, Christophe; Sinnaeve, Peter R.; Desmet, Walter
Abstract: Background: The optimal therapeutic strategy for ST-segment elevation myocardial infarction (STEMI) patients found to have multi-vessel disease (MVD) is controversial but recent data support complete revascularisation (CR). Whether CR should be completed during the index admission or during a second staged admission remains unclear. Our main objective was to measure rates of major adverse cardiovascular events (MACEs) during the waiting period in STEMI patients selected for staged revascularisation (SR), in order to determine the safety of delaying CR. For completeness, we also describe 30-day and long-term outcomes in STEMI patients with MVD who underwent in-hospital CR. Methods: A single-centre retrospective analysis of 931 STEMI patients treated by primary percutaneous coronary intervention (PCI) identified 397 patients with MVD who were haemodynamically stable and presented within 12 hours of chest pain onset. Of these, 191 underwent multi-vessel PCI: 49 during the index admission and 142 patients undergoing a strategy of SR. Results: Our main finding was that waiting period MACE were 2% (three of 142) in patients allocated to SR (at a median of 31 days). In patients allocated to in-hospital CR, 30-day MACE rates were 10% (five of 49). During a median follow up of 39 months, all-cause mortality was 7.0% vs. 28.6%, and cardiac mortality was 2% vs. 8%, in patients allocated to SR or CR, respectively. Conclusions: Patients with STEMI and MVD who, based on clinical judgement, were allocated to a second admission SR strategy had very few adverse events during the waiting period and excellent long-term outcomes.